The Decrease of Uch-L1 Activity Is a Common Mechanism Responsible for Aβ 42 Accumulation in Alzheimer’s and Vascular Disease - Guglielmotto, Michela; Monteleone, Debora; Vasciaveo, Valeria; Repetto, Ivan Enrico; Manassero, Giusi; Tabaton, Massimo; Tamagno, Elena (Frontiers in Aging Neuroscience, 2017)
Alzheimer's disease (AD) is a multifactorial pathology causing common brain spectrum disorders in affected patients. These mixed neurological disorders not only include structural AD brain changes but also cerebrovascular lesions. The main aim of the present issue is to find the factors shared by the two pathologies. The decrease of ubiquitin C-terminal hydrolase L1 (Uch-L1), a major neuronal enzyme involved in the elimination of misfolded proteins, was observed in ischemic injury as well as in AD, but its role in the pathogenesis of AD is far to be clear. In this study we demonstrated that Uch-L1 inhibition induces BACE1 up-regulation and increases neuronal and apoptotic cell death in control as well as in transgenic AD mouse model subjected to Bengal Rose, a light-sensitive dye inducing that induces a cortical infarction through photo-activation. Under the same conditions we also found a significant activation of NF-κB. Thus, the restoration of Uch-L1 was able to completely prevent both the increase in BACE1 protein levels and the amount of cell death. Our data suggest that the Uch-L1-mediated BACE1 up-regulation could be an important mechanism responsible for Aβ peptides accumulation in vascular injury and indicate that the modulation of the activity of this enzyme could provide new therapeutic strategies in AD.